Practical financial management - Lasher, William. (South-Western College, 2000)
This book is divided into six parts: Introduction to financial management; Discounted cash flow and the value of securities; Business investment decisions-capital budgeting; Long-term financing issues; Operations issues-working capital management and planning; and Current topics in financial management.